1989
DOI: 10.1093/jaoac/72.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay for T-2 Toxin Metabolites in Urine

Abstract: A direct competitive enzyme-linked immunosorbent assay (ELISA) for determination of total T-2 toxin metabolites in urine was developed. The assay involves coating anti-3-acetyl-neosolaniol-hemisuccinate- bovine serum albumin conjugate (anti-3-Ac-NEOS-HS-BSA) antibody to the ELISA plate and using 3-Ac-NEOS-HS-peroxidase as the enzyme marker. Competitive ELISA revealed that the antibody had good cross-reactivity with acetyldiacetoxyscirpenol (Ac-DAS), T-2 tetraol tetraacetate, 3'-OH-Ac-T-2, 3-Ac-NEOS, and 3,4,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…For the determination of total type-A TCTC, an indirect ELISA was used. This assay quantitatively determines all of the type-A TCTC after converting them to T-2 tetraacetate (15,24). The analytical recoveries of T-2 toxin added to a blank corn sample at 0.1-, 0.5-, 2-, and 5-ppm levels were 123, 94, 98, and 83.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the determination of total type-A TCTC, an indirect ELISA was used. This assay quantitatively determines all of the type-A TCTC after converting them to T-2 tetraacetate (15,24). The analytical recoveries of T-2 toxin added to a blank corn sample at 0.1-, 0.5-, 2-, and 5-ppm levels were 123, 94, 98, and 83.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Sep-Pak C-18 reverse-phase cartridge was obtained from Waters Associates (Milford, Mass.). Specific antibodies against mycotoxins and related immunochemical reagents were prepared in our laboratory (4,15,31). All other chemicals and organic solvents were either analytical grade or high-performance liquid chromatography (HPLC) grade.…”
Section: Materlals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods that can simultaneously detect all type A trichothecenes are rare. Wei and Chu (1987), Fan et al (1988) and Lee, Wei, and Chu (1989) reported immunochemical methods to detect type A trichothecenes, but none of these methods can detect all type A trichothecenes. Our research has extended these findings by further optimizing the preparation of an antigen to type A trichothecene skeletons.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium tricinctum 696 (now reclassified as F. sporotrichioides) in cracked corn at 15ЊC under the conditions described earlier (10). Acetyl-T-2 toxin (Ac-T-2), T-2 tetraol tetraacetate (T-2-4ol-4Ac), 3-Ac-NEOS, hemisuccinate (HS) of 3-Ac-NEOS, and 3-Ac-NEOS-HS-horseradish peroxide (HRP) conjugate were prepared according to methods described previously (20,41). DON was produced by F. graminearum NRRL 5883 in cracked corn at 25ЊC under the conditions described by Vesonder et al (39).…”
Section: Materials T-2 Toxin Was Produced Bymentioning
confidence: 99%